Quality of life in anterior cruciate ligament-deficient individuals: a systematic review and meta-analysis - Filbay, S; Culvenor, A; Ackerman, I; Russell, T; Crossley, K (BMJ Publishing Group, 2015)
Background Physical and psychological impairments impacting quality of life (QOL) are common following ACL reconstruction. Rehabilitation alone is an effective alternative to reconstruction for some patients, warranting the investigation of QOL in ACL-deficient individuals. Purpose To report and compare QOL in ACL-deficient individuals with population norms and ACL-reconstructed groups, and investigate relationships between participant characteristics and QOL. Study design Systematic review and meta-analysis. Methods We systematically identified and methodologically appraised all studies reporting QOL in ACL-deficient individuals ≥5 years following ACL rupture. Knee-related and health-related QOL scores in ACL-deficient cohorts were compared to ACL-reconstructed groups using a random-effects meta-analysis. Descriptive comparisons were made with population norms. Results Eleven studies reported QOL in 473 ACL-deficient individuals, a mean of 10 (range 5–23) years following ACL rupture. Eight studies reported knee-related QOL using the Knee injury and Osteoarthritis Outcome Score QOL subscale (KOOS-QOL); scores (mean±SD) ranging from 54±17 to 77±22 were impaired compared to population norms. Health-related QOL, measured with the SF-36 domain scores in five studies, was similar to population norms, but impaired compared to physically active populations. Meta-analysis revealed no significant differences in KOOS-QOL (mean difference (95% CI) 2.9 (−3.3 to 9.1)) and SF-36 scores (for all SF-36 domains except Vitality) between ACL-deficient and ACL-reconstructed groups. Conclusions This systematic review found impaired knee-related QOL in ACL-deficient individuals ≥5 years after ACL rupture, compared to population norms. Meta-analysis revealed similar knee-related QOL in ACL-deficient and ACL-reconstructed groups, and no difference in health-related QOL scores for seven of the eight SF-36 domains.